Snowline-driven glacier dynamics across the Indian Himalayas - Deva Jefflin A R; Chandre Gowda C; Geetha Priya M; Sushil Kumar Singh (International Journal of Remote Sensing, 2026)

Effects of a Mixed Biomass of Thalassiosira weissflogii and Chaetoceros calcitrans as a Functional Feed Additive for Pacific White Shrimp (Penaeus vannamei) - A. Gangaiyammal; K. Anandhi; M. Geetha; G. Brindha; Mukul Machhindra Barwant; Usman Mohammed Ali (Marine Biotechnology, 2026)

Seismic fragility assessment of reinforced concrete bridges: a comprehensive review of methodologies, isolators, and soil structure interaction - Ashwini Satyanarayana; Dushyanth V. Babu R; H. M. Sheethal; L. Geetha (Innovative Infrastructure Solutions, 2026)

Optimizing Crop Yield Prediction and Suitability using Reinforcement Learning and Context Aware Multi-Channel Networks in IoT-Enabled Smart Agriculture - J. Jencewin; M. R. Geetha (Water Resources Management, 2026)

Personalizing treatment of pancreatitis-associated chronic pain: the need for an integrated omics approach - Cole Myers; Cheyenna M. Espinoza; Aaron Clarke; Elizabeth R. Lusczek; Feng Xie; Brian T. Steffen; Zeribe C. Nwosu; Guru Trikudanathan; Geetha Saarunya; Melena Bellin; Gregory Beilman (Inflammation Research, 2026)
Background Chronic pancreatitis (CP) is a progressive inflammatory disorder characterized by debilitating chronic pain and substantial healthcare burden. Pain mechanisms in CP are heterogeneous and incompletely integrated into clinical decision-making. This narrative review synthesizes data from human CP cohorts and complementary experimental models to summarize inflammatory, neuropathic, and metabolic drivers of pancreatitis-associated pain and to evaluate how integrated multi-omics approaches may enable mechanism-based precision management. Current treatment relies on lifestyle modification, anatomy-guided interventions, stepwise pharmacologic escalation, and surgery for refractory cases. Emerging ion-channel–targeted therapies show promise, but inconsistent patient selection and limited biomarker guidance constrain therapeutic precision. Findings CP-associated pain arises from convergent inflammatory, neuroimmune, neuropathic, and metabolic pathways that promote peripheral and central sensitization with sustained neuroplastic remodeling. Advances in clinical phenotyping have improved characterization of pain subtypes; however, integration of biologic data remains limited. Genetic association studies increasingly implicate pathways linked to severe or persistent pain phenotypes. Omics investigations have identified candidate genomic, proteomic, and metabolomic signals that may support biologically informed stratification and treatment prediction. Nevertheless, most studies are cross-sectional, modality-specific, and derived from heterogeneous cohorts with inconsistent endpoints and limited external validation. Conclusions Integration of rigorous clinical phenotyping with longitudinal, multi-omics modeling provides a framework for developing testable, mechanism-based biomarkers to guide personalized analgesic and procedural strategies while supporting opioid-sparing care. Priorities include harmonization of multicenter datasets, standardized and longitudinal pain outcome measurement, expanded paired biospecimen collection, and external validation of predictive models. Such efforts may enable biologically grounded pain stratification and facilitate translation of biomarker-guided decision tools into routine clinical practice.

Application of natural compounds with antimicrobial and antiviral properties - Bharat Krishna M; Geetha Shanmugam (Natural Product Research, 2026)

Thermal Conversion of Sugarcane Bagasse to Biochar and Its Application in Treatment of Methylene Blue Contaminated Water - T. Geetha; John K Smitha; Litty Mathew Irimpan; Manju Sebastian; V. Geetha; C. J. Theresa; Bincy Joseph; M. Nancy; K. Nimmy (Sugar Tech, 2026)

Trace-level electrochemical detection of organic pollutant metol in environmental samples using MIL-101(Cr)@F-MWCNTs nanocomposite - Bhakti Kulkarni; Thangavelu Kokulnathan; Tzyy-Jiann Wang; Mysoon M. Al-Ansari; R. Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2025)

Development of a multi-model framework for standardized groundwater index computation: Application to Andhra Pradesh and Telangana states - Asha Farsana M; Bharath Kumar Reddy Kadapala; Satya Geetha Vimala Channa; Abdul Hakeem K; Chandrasekar K (Groundwater for Sustainable Development, 2025)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

Genetic diversity, morphological variation and biochemical profiling of dolichos bean: a study for crop improvement - Krishnan Deepana; K. Geetha; P. Jeyaprakash; M. Sangeetha; K. Govindan; M. S. Aneesa Rani; S. Srividhya (Genetic Resources and Crop Evolution, 2025)

Correction to: Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

Integrating solid stem and multiple disease resistance for developing climate-resilient wheat (Triticum aestivum L.) - P. Shajitha; R. Nisha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; K. Gajalakshmi; Niharikha Mallick; Prashanth Babu; Rajbir Yadav; S. Vijaishree; K. Akileshwaran; John Peter; et al. (Cereal Research Communications, 2025)

Mapping coastal urbanization impacts with object-based image classification and land use/land cover change detection: A focus on sustainable development - C.S. Manikandababu; Nada Alzaben; Mashael Maashi; M. Geetha (Journal of South American Earth Sciences, 2025)

Cisgenics–An advanced breeding technique for Fruit crop amelioration - V. Boomika; M. S. Aneesa Rani; K. S. Vijai Selvaraj; P. Irene Vethamoni; R. Kalaiyarasi; P. Geetha (Euphytica, 2025)

Chronicles of Glacier Changes of Two Decades in Tons Sub-Basin, West-Central Himalaya, Using Geospatial Techniques - Dhanush S; Geetha Priya M (Journal of the Indian Society of Remote Sensing, 2025)

The Aegilops ventricosa derived 2NvS translocation for enhanced defense against multiple diseases in wheat - R. Nisha; P. Shajitha; M. Sivasamy; P. Jayaprakash; V. K. Vikas; Shailendra Jha; Niharika Mallick; Rajbir Yadav; S. C. Bhardwaj; O. P. Gangwar; S. Vijaishree; M. Geetha; et al. (Journal of Crop Science and Biotechnology, 2025)

First metabolic profiling of Indian wild edible mushroom Amanita hemibapha reveals antimicrobial compounds that infers selective activity against gram-positive human pathogens - Gama Mohan M Geetha; Anagha Bindu; Ratheesh Sugathan; Vipin Mohan Dan; Chittethu Kunjan Pradeep (Natural Product Research, 2025)

Influence of hydrotherapy on change in weight: a narrative review - M. Y. Manju; Geetha B. Shetty; K. J. Sujatha; Prashanth Shetty (International Journal of Biometeorology, 2025)

The Dolichos bean: a versatile legume with potential to address food security challenges and strategies for improvement - Krishnan Deepana; K. Geetha; P. Jeyaprakash; M. Sangeetha; K. Govindan (Genetic Resources and Crop Evolution, 2025)

Effects of Metarhizium anisopliae on the histochemistry and enzymatic activities of Helicoverpa armigera (Hübner, 1809) - Yamini R; Shanmugam P.S; Murugan M; Geetha N; Meenakshi P; Srinivasan T; Premalatha K; Kandan A; Sathiyaraj G; Vivekanandhan P (Biocatalysis and Agricultural Biotechnology, 2024)

A grid-wise approach for accurate computation of Standardized Runoff Index (SRI) - Bharath Kumar Reddy Kadapala; M. Asha Farsana; C.H. Geetha Vimala; Saksham Joshi; K. Abdul Hakeem; P.V. Raju (Science of The Total Environment, 2024)

Preparation and characterization of activated carbon from corn cob by chemical activation and their adsorption of brilliant green dye from wastewater - Sakthivel Kumaravel; M. Geetha; Theophile Niyitanga; D. Senthil Kumar; Mysoon M. Al-Ansari; R. Mythili; Sanjeevamuthu Suganthi; L. Guganathan; A. Murugan; S. Ragupathy (Process Safety and Environmental Protection, 2024)

Digital assessment of post-harvest Nendran banana for faster grading: CNN-based ripeness classification model - P.L. Arunima; Pratheesh P. Gopinath; P.R. Geetha Lekshmi; M. Esakkimuthu (Postharvest Biology and Technology, 2024)

A comprehensive analysis on nutritional composition, functional properties, antioxidant and enzyme inhibitory potential of selected minor millet grains - C. Jenipher; V.P. Santhi; S. Amalraj; V.Sathia Geetha; S.S. Gurav; M.G. Kalaskar; M. Ayyanar (South African Journal of Botany, 2024)

Quinoline-quinoline schiff-base as an effective chromogenic, fluorogenic, and smartphone assisted RGB detection of Pb2+ ion in near aqueous medium - Kathirvel R; Poongodi M; Vetriarasu V; Vivekanandan K.E; Selvakumar K; Sami Al Obaid; Arivalagan Pugazhendhi; Geetha Venkatesan (Environmental Research, 2024)

A concise review on biorefinery remedies for biomethanol production and processing - Mayur Thakare; Soumya Pandit; Chetan Pandit; Subhasree Ray; Abdullah M. Alkahtani; Khulood Fahad Alabbosh; Nishant Ranjan; S.J. Geetha; Sanket J. Joshi (Biocatalysis and Agricultural Biotechnology, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

Chlamydomonas as a model system for studying the relevance of plant genes for their involvement in multiple individual and combined stresses: a study unravelling PgCuZnSOD and PgAPX gene functions - H. M. Mamrutha; Geetha Govind; Hema Ramanna; Radha Sivarajan Sajeevan; A. N. Lokesha; Muthappa Senthil-Kumar; Karaba N. Nataraja (Plant Physiology Reports, 2024)

Secure water quality prediction system using machine learning and blockchain technologies - Geetha Jenifel M (Journal of Environmental Management, 2024)

Neuroprotective effect of chia seed oil nanoemulsion against rotenone induced motor impairment and oxidative stress in mice model of Parkinson’s disease - K. M. Geetha; Jyotsna Shankar; Barnabas Wilson (Advances in Traditional Medicine, 2023)

Template free synthesis of CuO nanocomposite for catalytic hydrogenation of CO2 - Haseena Onthath; Mostafa H. Sliem; Mithra Geetha; Kishor Kumar Sadasivuni; Aboubakr M. Abdullah; Bijandra Kumar (Journal of Environmental Management, 2023)

First Record of the Thai Bobtail Squid, Euprymna hyllebergi Nateewathana, 1997 (Cephalopoda: Sepiolidae) from the Arabian Sea - Vellathi Venkatesan; Kurichithara K. Sajikumar; Nikarthil S Jeena; Summaya Rahuman; Puthenpurakkal S. Alloycious; Konnoth M. Jestin Joy; Kolliyil S. Mohamed; Geetha Sasikumar (Thalassas: An International Journal of Marine Sciences, 2023)

Elucidating the role of effector protein as biomarker for enhanced resistance against pearl millet downy mildew disease - Shiva Hadimani; Shreya M. Joshi; Nagaraj Geetha; Hunthrike Shekar Shetty; Sudisha Jogaiah (Physiological and Molecular Plant Pathology, 2023)

Acacia furnesiana plant as a novel green source for the synthesis of NiFe2O4 magnetic nanocatalyst and as feedstock for sustainable high quality biofuel production - Veeranna R. Kattimani; K.V. Yatish; K. Pramoda; M. Sakar; R. Geetha Balakrishna (Fuel, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Novel inducible promoter DREB1G cloned from date palm exhibits high fold expression over AtRD29 to drought and salinity stress - Preshobha Kodackattumannil; Kenna Whitley; Shina Sasi; Geetha Lekshmi; Saranya Krishnan; Salima Al Senaani; Martin Kottackal; Khaled M. A. Amiri (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Right and timely expression of the stress regulatory genes is required for plants to compete against abiotic stresses; it necessitates the isolation and characterization of stress-responsive promoters for improving crops' tolerance to abiotic stresses. Dehydration Responsive Element Binding (DREB) regulates the expression of numerous stress-responsive genes in plants and leads an inevitable role in the adaptation of plants to abiotic stresses. In this study, the promoter region of Phoenix dactylifera (Date palm, a major fruit crop of the arid region) PdDREB1G gene was isolated and characterized for the first time. A comparison of the activity of two promoter fragments, 880 bp (DS) and 1.6 kb (DF) of PdDREB1G to AtRD29A was performed. Histochemical assay displayed remarkable GUS staining and RT-qPCR analysis confirmed the induction of GUS expression in T 3 plants of transformed tobacco subjected to different abiotic stresses. Furthermore, compared with the widely used AtRD29A promoter, the relative expression of GUS in leaves by DS and DF was three and twofold higher under salt stress, respectively, while it was twofold in polyethylene glycol (PEG) and abscisic acid (ABA) for DS. Under SA stress, DF and DS displayed 1.5 and onefold expression in leaves, respectively. In the root, DS showed a fourfold increased expression in salt, threefold in PEG and ABA, and twofold in SA. Hence, the DS promoter characterized in the present study becomes a choice over RD29A for abiotic stress responses and is useful to develop stress-tolerant transgenic plants by inducing the expression of stress-inducible genes on stress.

Neisseria montereyensis sp. nov., Isolated from Oropharynx of California Sea Lion (Zalophus californianus): Genomic, Phylogenetic, and Phenotypic Study - Dmitriy V. Volokhov; Tatiana A. Zagorodnyaya; Vyacheslav A. Furtak; Geetha Nattanmai; Linnell Randall; Sherly Jose; Yamei Gao; Frances M. Gulland; Tobias Eisenberg; Pierluigi Delmonte; Jochen Blom; Kara K. Mitchell (Current Microbiology, 2023)

Spatial variability of trace gases (NO2, O3 and CO) over Indian region during 2020 and 2021 COVID-19 lockdowns - Vasudevan Geetha Vignesh; Chaithanya D. Jain; K. Saikranthi; M. Venkat Ratnam (Environmental Monitoring and Assessment, 2023)

Hidden pleiotropy of agronomic traits uncovered by CRISPR-Cas9 mutagenesis of the tyrosinase CuA-binding domain of the polyphenol oxidase 2 of eggplant - Preshobha Kodackattumannil; Geetha Lekshmi; Martin Kottackal; Shina Sasi; Saranya Krishnan; Salima Al Senaani; Khaled M. A. Amiri (Plant Cell Reports, 2023)

Study on the workability, mechanical properties of fish tail palm fibre reinforced concrete-emphasis on fibre content and fibre length - R. Vijayalakshmi; M. Vaishnavi; R. Geetha (European Journal of Environmental and Civil Engineering, 2023)

Development of in vitro pollen germination protocol for recalcitrant triticale pollen (X Triticosecale Wittmack) - P. Jayaprakash; John Peter; P. Shajitha; V. Balaji; R. Nisha; M. Geetha; V. K. Vikas; M. Sivasamy (Cereal Research Communications, 2023)

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Hawaiian flying squid Nototodarus hawaiiensis (Cephalopoda: Ommastrephidae) in the Arabian Sea: range extension, age, and growth - Kurichithara Kunjumony Sajikumar; Pappurajam Laxmilatha; Sneha Vargheese; Pulukkayi Pranav; Vellathi Venkatesan; Ravindranathapanicker Vidya; Puthenpurakkal Simon Alloycious; K. M. Jestin Joy; Geetha Sasikumar (Marine Biodiversity, 2023)

Pepper-acquired resistance induced by salicylic acid against Chilli Veinal Mottle Virus - Suveditha Subhash; Gouribidanur Ashwathappa Geetha; Kodthalu Seetharamaiah Shivashankar; M. Krishna Reddy (Indian Phytopathology, 2022)

Mass balance estimation of Mulkila glacier, Western Himalayas, using glacier melt model - Geetha Priya M.; Chandhana Guruprasad; Deeksha Gopal; Suresh Devaraj (Environmental Monitoring and Assessment, 2022)

Techno-economic evaluation of Asian seabass (Lates calcarifer) nursery rearing in small net cages (hapas) under different coastal salinities - M. Kumaran; K. P. Kumaraguru Vasagam; R. Subburaj; P. R. Anand; K. Ramachandran; R. Geetha; D. Deboral Vimala; R. Anandaraja; M. Jayanthi; C. V. Sairam (Aquaculture International, 2022)

Differential Multi-cellularity Is Required for the Adaptation for Bacillus licheniformis to Withstand Heavy Metals Toxicity - Channarayapatna-Ramesh Sunilkumar; Emmanuel Stephen-Victor; Kishore Babu Naripogu; J. Samanth Kumar; Bettadapura Rameshgowda Nuthan; K. M. Marulasiddaswamy; Kukkundoor Ramachandra Kini; Nagaraja Geetha (Indian Journal of Microbiology, 2021)

Characterisation of an individual of the giant form of the purpleback flying squid Sthenoteuthis oualaniensis (Cephalopoda: Ommastriphidae) in the Arabian Sea and its biological descriptors - Kurichithara K. Sajikumar; Theparambil M. Najmudeen; Nadakkal Ragesh; N. S. Jeena; Summaya Rahuman; K. T. Sadanandan Sunil; Geetha Sasikumar; Kolliyil S. Mohamed (Molluscan Research, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Additive main effects and multiplicative interaction analyses of yield performance in rice genotypes for general and specific adaptation to salt stress in locations in India - S. L. Krishnamurthy; P. C. Sharma; D. K. Sharma; Y. P. Singh; V. K. Mishra; D. Burman; B. Maji; S. Mandal; S. K. Sarangi; R. K. Gautam; P. K. Singh; K. K. Manohara; et al. (Euphytica, 2021)
The aim of this study was to identify stable rice genotypes tolerant to a salt stress environment and to identify ideal mega-environments using AMMI (additive main effects and multiplicative interaction) stability model analysis. A total of 13 rice genotypes and three salt tolerance checks were evaluated across 13 salt stress locations (alkaline and saline) for the two kharif seasons of 2014 and 2015. Genotype CSR 36 (CHK3) was found to be the most ideal of those tested. Genotypes CHK2 (CST 27) and IR 87952-1-1-1-2-3-B (G05) were found to be the most stable, with above average yields. The check CSR 36 (CHK3) genotype was the best performer in the majority of the environments studied, followed by CSR 27 (CHK2) and IR 87952-1-1-1-2-3-B (G05) which were the best genotypes in the mega-environment consisting of 21 environments evaluated across stress locations and year combinations. Overall, the most promising genotype (IR 87952-1-1-1-2-3-B) had high mean yield and stability and could be used for commercial cultivation or used as donor for breeding programs across salt-affected soils. The genotypes GN13 (IR 87938-1-1-2-1-3-B) and GN11 (IR 87938-1-2-2-1-3-B) showed 60–80% yield advantage at specific salt stress locations, showing that these genotypes could be used for specific environments of salt-affected soils in India.

Contemporary Updates on the Physiology of Glucagon like Peptide-1 and Its Agonist to Treat Type 2 Diabetes Mellitus - Anju Das; K. M. Geetha; Iswar Hazarika (International Journal of Peptide Research and Therapeutics, 2020)

Recursive partitioning algorithm in water quality prediction - M. Geetha Jenifel; R. Jemila Rose (International Journal of Environmental Science and Technology, 2020)

Characterization of inertia gravity waves and associated dynamics in the lower stratosphere over the Indian Antarctic station, Bharati (69.4°S, 76.2°E) during austral summers - N. Koushik; Karanam Kishore Kumar; K. V. Subrahmanyam; Geetha Ramkumar; I. A. Girach; M. Santosh; K. Nalini; M. Nazeer; P. R. Shreedevi (Climate Dynamics, 2019)

Iron-based flow batteries to store renewable energies - Anarghya Dinesh; Sharon Olivera; Krishna Venkatesh; Mysore Sridhar Santosh; Murugesan Geetha Priya; Inamuddin; Abdullah M. Asiri; Handanahally Basavarajaiah Muralidhara (Environmental Chemistry Letters, 2018)

Range extension of a bathypelagic squid, Bathyteuthis bacidifera (Cephalopoda: Bathyteuthidae), to the south Arabian Sea with special reference to its age and growth pattern - K. K. Sajikumar; A. I. Arkhipkin; V. Venkatesan; K. M. Jestin Joy; C. P. Binesh; Geetha Sasikumar; Kolliyil S. Mohamed (Marine Biodiversity, 2018)

Evaluation of genetic stability using FRAPD markers as novel method along with antioxidant and anti-diabetic properties of micropropagated Salacia chinensis L. - Majid Bagnazari; M. G. Mahesh; Mehdi Saidi; K. R. Kini; H. S. Prakash; N. Geetha (Acta Physiologiae Plantarum, 2018)

New camphor hybrids: lipophilic enhancement improves antimicrobial efficacy against drug-resistant pathogenic microbes and intestinal worms - Ramalingam Peraman; Amit K. Tiwari; M. Geetha Vani; J. Hemanth; Y. Geetha Sree; K. Karthik; Charles R. Ashby; Y. Padmanabha Reddy; Raghuveer V. Pemmidi (Medicinal Chemistry Research, 2018)

Characterization and genome comparison of an Indian isolate of bidensovirus infecting the silkworm Bombyx mori - Tania Gupta; Katsuhiko Ito; Keiko Kadono-Okuda; Geetha N. Murthy; E. Vijaya Gowri; Kangayam M. Ponnuvel (Archives of Virology, 2018)

Inhibitory activity of bio-active compounds isolated from Anadara granosa in shrimp health management - D. Sunil Kumar; P. Janakiram; M. Murali Krishna Kumar; G. Krishna Geetha (World Journal of Microbiology and Biotechnology, 2017)

Effect of phycochemical coated silver nanocomplexes as novel growth-stimulating compounds for plant regeneration of Alternanthera sessilis L. - P. Venkatachalam; S. Malar; M. Thiyagarajan; P. Indiraarulselvi; N. Geetha (Journal of Applied Phycology, 2017)

Enhanced anti-fibrogenic effects of novel oridonin derivative CYD0692 in hepatic stellate cells - Fredrick J. Bohanon; Xiaofu Wang; Brittany M. Graham; Anesh Prasai; Sadhashiva J. Vasudevan; Chunyong Ding; Ye Ding; Geetha L. Radhakrishnan; Cristiana Rastellini; Jia Zhou; Ravi S. Radhakrishnan (Molecular and Cellular Biochemistry, 2015)

Multi-target drugs to address multiple checkpoints in complex inflammatory pathologies: evolutionary cues for novel “first-in-class” anti-inflammatory drug candidates: a reviewer’s perspective - Geetha Mathew; M. K. Unnikrishnan (Inflammation Research, 2015)

Genetic clustering of recent classical swine fever virus isolates from Karnataka, India revealed the emergence of subtype 2.2 replacing subtype 1.1 - D. B. Shivaraj; S. S. Patil; D. Rathnamma; D. Hemadri; S. Isloor; S. Geetha; G. B. Manjunathareddy; M. R. Gajendragad; H. Rahman (VirusDisease, 2015)

Coregulation of host–response genes in integument: switchover of gene expression correlation pattern and impaired immune responses induced by dipteran parasite infection in the silkworm, Bombyx mori - Anitha Jayaram; Appukuttan Nair R. Pradeep; Arvind K. Awasthi; Geetha N. Murthy; Kangayam M. Ponnuvel; Sirigineedi Sasibhushan; Guruprasad C. Rao (Journal of Applied Genetics, 2014)

Plasma anti-α-galactoside antibody binds to serine- and threonine-rich peptide sequence of apo(a) subunit in Lp(a) - M. Geetha; V. Kalaivani; P. S. Sabarinath; P. S. Appukuttan (Glycoconjugate Journal, 2014)

Growth response of Casuarina equisetifolia Forst. rooted stem cuttings to Frankia in nursery and field conditions - A Karthikeyan; K Chandrasekaran; M Geetha; R Kalaiselvi (Journal of Biosciences, 2013)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Bacillus thuringiensis Isolates from Great Nicobar Islands - R. Asokan; H. M. Mahadeva Swamy; Ajanta Birah; Geetha G. Thimmegowda (Current Microbiology, 2013)

Treatment of vegetable oil mill effluent using crab shell chitosan as adsorbent - M. Geetha Devi; Z. S. Shinoon Al-Hashmi; G. Chandra Sekhar (International Journal of Environmental Science and Technology, 2012)

Studies on antioxidant status in Mugil cephalus in response to heavy metal pollution at Ennore estuary - E. Padmini; M. Usha Rani; B. Vijaya Geetha (Environmental Monitoring and Assessment, 2009)

Functional characterization of Nicotiana benthamiana homologs of peanut water deficit-induced genes by virus-induced gene silencing - M. Senthil-Kumar; Geetha Govind; Li Kang; Kirankumar S. Mysore; M. Udayakumar (Planta, 2007)

Effects of presowing treatments, desiccation and storage conditions on germination of Strychnos nux-vomica seeds, a valuable medicinal plant - V. Sivakumar; R. Anandalakshmi; R. R. Warrier; M. Tigabu; P. C. Odén; S. N. Vijayachandran; S. Geetha; B. G. Singh (New Forests, 2006)

Immunomodulatory effects of seabuckthorn (Hippophae rhamnoides L.) against chromium (VI) induced immunosuppression - S. Geetha; Vandana Singh; M. Sai Ram; G. Ilavazhagan; P. K. Banerjee; R. C. Sawhney (Molecular and Cellular Biochemistry, 2005)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

A rapid protocol for somatic embryogenesis from immature leaflets of groundnut (Arachis hypogaea L.) - P. Venkatachalam; P. B. Kavi Kishor; N. Geetha; M. Thangavelu; N. Jayabalan (In Vitro Cellular & Developmental Biology - Plant, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Separation of bovine heart galactose lectin from endogenous glycoproteins co-purified with the lectin during affinity chromatography - P. S. Appukuttan; K. I. Annamma; M. Geetha; P. L. Jaison (Journal of Biosciences, 1998)

Parasites, predators and other arthropods associated withMusca domestica and other flies breeding in bovine manure - M. Geetha Bai; T. Sankaran (BioControl, 1977)